2000
DOI: 10.5860/crl.61.5.400
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of the Doctorate among Small College Library Directors

Abstract: Although a doctorate provides a library director with little practical assis tance toward fulfilling his or her job, many college and university admin istrators seem to expect library directors to have one. The presence of the doctorate has been studied extensively within ARL institutions, but not within small colleges. This article explores the presence of the doc torate among small college library directors, considering gender and tenure in addition to size of the library, the college, and the library staff.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…27 McCracken described that higher education was compulsory for academic library leadership and found that 60 percent of the library director positions were occupied by women in liberal arts colleges. 28 Martin investigated the positive effects of the transformational leadership styles on the professional lives of academic library directors, deans, and librarians and concluded that female library leaders also used the transformational leadership skills (individualized consideration, idealized influence, inspirational motivation, intellectual stimulation) in their roles as leaders. Similar to their male counterparts, they used these leadership styles to build relationships and create trust with coworkers, mentors, and others.…”
Section: Attributes Of Successful Women Library Leadershipmentioning
confidence: 99%
“…27 McCracken described that higher education was compulsory for academic library leadership and found that 60 percent of the library director positions were occupied by women in liberal arts colleges. 28 Martin investigated the positive effects of the transformational leadership styles on the professional lives of academic library directors, deans, and librarians and concluded that female library leaders also used the transformational leadership skills (individualized consideration, idealized influence, inspirational motivation, intellectual stimulation) in their roles as leaders. Similar to their male counterparts, they used these leadership styles to build relationships and create trust with coworkers, mentors, and others.…”
Section: Attributes Of Successful Women Library Leadershipmentioning
confidence: 99%
“…It is not clear whether a second Master’s degree or Doctorate (in non-LIS-related disciplines) was necessary for them to assume a director position, or if library directors who do not have a doctorate are at a disadvantage. According to McCracken (2000), although academic degrees cannot replace administrative aptitude, creativity, and the knowledge to be a successful university library director, some library directors would advise those they mentor to pursue a Doctoral degree for career-advancement reasons.…”
Section: Research Populationmentioning
confidence: 99%
“…He reported that 20 percent of the library directors (n = 80) who responded to his study held a doctorate and 40 percent held a second master's degree. 24 When McCracken categorized library directors by gender and education, he found that more men (n = 11) than women (n = 5) held PhDs. This was consistent for directors who held a second master's degree; 25 more men (n = 20) held a second master's degree than women (n = 11).…”
Section: Library Director Credentials-current Perspectives (1990-presmentioning
confidence: 99%